Political control and policy-making uncertainty in executive orders: the implementation of environmental justice policy. (28th March 2018) - Provost, Colin; Gerber, Brian J.
Abstract: Environmental justice (EJ) has represented an important equity challenge in policymaking for decades. President Clinton's executive order (EO) 12898 in 1994 represented a significant federal action, requiring agencies to account for EJ issues in new rulemakings. We examine the impact of EO 12898 within the larger question of how EO are implemented in complex policymaking. We argue that presidential preferences will affect bureaucratic responsiveness and fire alarm oversight. However, EJ policy complexity produces uncertainty leading to bureaucratic risk aversion, constraining presidential efforts to steer policy. We utilise an original data set of nearly 2, 000 final federal agency rules citing EO 12898 and find significant variation in its utilisation across administrations. Uncertainty over the nature of the order has an important influence on bureaucratic responsiveness. Our findings are instructive for the twin influences of political control and policy-making uncertainty and raise useful questions for future EJ and policy implementation research.